A diffuse lung emphysema, severe pulmonary hypertension and lack of airflow limitation. (2017) - Faure, Morgane; Gomez, Emmanuel; Dorfmüller, Peter; Mandry, Damien; Canuet, Matthieu; Kessler, Romain; Chabot, François; Chaouat, Ari
Abstract: Pulmonary veno-occlusive disease is characterized by remodeling of pulmonary arteries, capillaries and venules. We report a case of diffuse lung emphysema and pulmonary veno-occlusive disease with the characteristic of having no airflow limitation. A very low diffusing capacity for carbon monoxide and results of high-resolution computed tomography of the chest suggested pulmonary veno-occlusive disease. The diagnosis was confirmed on histological analysis after lung transplantation. The combination of results of the computed tomography of the chest and the histological analysis suggested a relationship between diffuse lung emphysema and remodeling of pulmonary vessels. A distinctive pattern of mild-to-moderate airflow limitation in patients with chronic obstructive pulmonary disease and severe pulmonary hypertension has been described. This observation of the combination of diffuse emphysema, pulmonary veno-occlusive disease and no airflow limitation supports further pathophysiological studies on severe pulmonary hypertension in chronic obstructive pulmonary disease.